Environmental and Medicinal Impacts of Clay - Umudi, Ese Queen; Umudi, Ogheneyoma Peter; Onojake, Lawson; Ehiedu, Chukwuwuikem Nathanael; Obukohwo, Innocent Erhieyovwe; Nwakwanogo, Blessing Ese (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The use of clay dates back to ancient times for nutritional, healing, and skincare purposes. Different clays are employed for other purposes. In the field of medicine, they are used as foams, binders, and scaffolds; in cosmetics, as absorbents, stabilizers, and emulsifiers; and pharmaceutically, as excipients, carriers, anti-toxins, and flavouring agents. Clays are also used as chemical agents for removing radioactive gases, heavy metals, and organic matter. However, the use of clay has its constraints. When ingested, clays can trap pollutants or toxins, depending on their source. In the case of peloids and ointments, podoconiosis, a disease associated with the long-term effect of bare feet on red clay soil in tropical regions, is a concern. Generally, clay is an important, natural, locally sourced material of great environmental benefit.